Menopause A Comic Treatment - Czerwiec, MK 1967-; Barry, Lynda 1956-; Burdock, Maureen 1970-; Camper, Jennifer; Councilor, Kc; Ewing, Leslie; Farmer, Joyce; Forney, Ellen; Fox, Ann M.; Geniza, Keet 1987-; Gregory, Roberta; Harrison, Teva 1976-2019; et al. (Penn State University Press, 2021)
Like so many other issues surrounding women's reproductive health, menopause has been treated as a cultural taboo. On the rare occasions that menopausal and perimenopausal women are depicted in popular culture, they are stereotypically cast as the butt of demeaning jokes that encourage us to laugh at their deteriorating bodies and emotional volatility. The result is that women facing menopause often feel isolated and ashamed. In a spirit of community and support, this collection of comics presents a different view of menopause that enables those experiencing it to be seen and to feel empowered.Balancing levity with sincerity, these comics unapologetically depict menopause and all its attendant symptoms, from hot flashes and vaginal dryness to forgetfulness, social stigma, anxiety, and shame. Created from a variety of perspectives, they represent a range of life experiences, ages, gender identities, ethnicities, and health conditions. The common thread uniting these stories is the affirmation that, while we can and should laugh at ourselves, no one should be ashamed of menopause. The comics in this book encourage us to share our experiences and to support one another, and ourselves, through self-care and community. Featuring works by a host of pioneering and up-and-coming comics artists, Menopause is a perfect foil to the simplistic, cheap-joke approach society at large has taken to this much-derided women's health issue. Readers will revel in the sly humor and universal truths found here.The contributors include Lynda Barry, Maureen Burdock, Jennifer Camper, KC Councilor, MK Czerwiec, Leslie Ewing, Joyce Farmer, Ellen Forney, Ann M. Fox, Keet Geniza, Roberta Gregory, Teva Harrison, Rachael House, Leah Jones, Monica Lalanda, Cathy Leamy, Ajuan Mance, Jessica Moran, Mimi Pond, Sharon Rosenzweig, Joyce Schachter, Susan Merrill Squier, Emily Steinberg, Nicola Streeten, A. K. Summers, Kimiko Tobimatsu, Carol Tyler, Shelley L. Wall, and Dana Walrath
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Mai 2021)
Keywords: COMICS & GRAPHIC NOVELS / Anthologies